From the New Editorial Collective (The Strategic Review for Southern Africa, 2022)
For this issue, we decided to respond, at rather short notice, to the war in Ukraine, which erupted after a somewhat long build-up just weeks before we completed the formation and constitution of the new editorial team. We are glad (and to some extent also proud) to offer you a special focus on the likely consequences of this war for Africa, presenting a variety of relevant perspectives. They underline that no states or societies are immune to its consequences, regardless of the position taken by governments. Geopolitics of this nature play out everywhere, no matter the degree to which governments elsewhere are (not) directly involved. It is also a reminder that in fundamental conflicts, even declared neutrality cannot avoid being seen (and may even be intended) as taking sides.